Mapping Experiences, 2nd Edition - Kalbach, James (O'Reilly Media, Inc., 2020)
Customers who have inconsistent experiences with products and services are understandably frustrated. But it's worse for organizations that can't pinpoint these problems because they're too focused on their own processes. This updated edition shows your team how to use alignment diagrams to turn valuable customer observations into actionable insight. You'll learn how this unique tool helps you visually map existing experience and envision future solutions. Designers, product and brand managers, marketing specialists, and business owners will discover how experience diagramming can help determine where business goals and customer perspectives intersect. Armed with this insight, you can provide the people you serve with real value. Examine recent changes in business-including the experience economy and trends like employee experience-along with the latest mapping techniques Learn how to create diagrams that account for multichannel experiences as well as ecosystem design Understand how facilitation is increasingly becoming part of mapping efforts, shifting the focus from a deliverable (a map) to one of actionability Explore the possibilities of applying mapping of all kinds to noncommercial settings, from fighting violent extremism to helping victims of domestic violence to confronting homelessness and more. Mapping experiences isn't just about product and service design; it's about understanding the human condition.